Adverse drug reactions associated with off-label use of ketorolac, with particular focus on elderly patients. An analysis of the Italian pharmacovigilance database and a population based study. (1st December 2016) - Viola, E.; Trifirò, G.; Ingrasciotta, Y.; Sottosanti, L.; Tari, M.; Giorgianni, F.; Moretti, U.; Leone, R.
ABSTRACT: Objective : This study aims to evaluate the frequency of off-label use of ketorolac in Italy and the related suspected adverse drug reactions (ADRs) reported. Methods : All the suspected cases associated with ketorolac recorded in the Italian Pharmacovigilance database were retrieved. Case evaluations were carried out in order to identify the off-label use of ketorolac. Moreover, an analysis of the inappropriate use of ketorolac was conducted using the 'Arianna' database of Caserta local health unit. Results : Up to December 2014, 822 reports of suspected ADRs related to ketorolac were retrieved in the database. The use of ketorolac was classified as off-label for 553 reports and on-label for 269. Among the off-label cases, 58.6% were serious compared to 39.0% of on-label cases. Gastrointestinal events were more frequently reported with off-label use. The analysis of Arianna database showed that 37, 729 out of 61, 910 patients, were treated off-label. Conclusions : The off-label use of ketorolac is widespread in Italy. This use increases the risk of serious ADR, especially in in case of prolonged duration of treatment and in elderly patients. The Italian Medicine Agency has decided to accurately monitor the appropriate use of the drug in Italy and, if necessary, take measures in order to minimize the risks.